2007
DOI: 10.1111/j.1365-2133.2007.08063.x
|View full text |Cite
|
Sign up to set email alerts
|

Topical application of acidified nitrite to the nail renders it antifungal and causes nitrosation of cysteine groups in the nail plate

Abstract: Acidified nitrite cream results in the formation of S-nitrosocysteine throughout the treated nail. Acidified nitrite treatment makes a nail antifungal. S-nitrosothiols, formed by nitrosation of nail sulphur residues, are the active component. Acidified nitrite exploits the nature of the nail barrier and utilizes it as a means of delivery of NO/nitrosothiol-mediated antifungal activity. Thus the principal obstacle to therapy in the nail becomes an effective delivery mechanism.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 32 publications
0
11
0
Order By: Relevance
“…These include as an anti-fungal agent in nails [139] and as a therapeutic agent in cystic fibrosis [128]. Topical administration of GSNO was shown to improve onychomycosis through an S-nitrosothiol-dependent mechanism [139]. This is particularly noteworthy, as the nail bed represents a physical barrier impenetrable to many anti-fungal agents.…”
Section: Use Of Gsno In Human Clinical Trialsmentioning
confidence: 99%
“…These include as an anti-fungal agent in nails [139] and as a therapeutic agent in cystic fibrosis [128]. Topical administration of GSNO was shown to improve onychomycosis through an S-nitrosothiol-dependent mechanism [139]. This is particularly noteworthy, as the nail bed represents a physical barrier impenetrable to many anti-fungal agents.…”
Section: Use Of Gsno In Human Clinical Trialsmentioning
confidence: 99%
“…Especially toxic are the products of the interactions between ROS and RNS, such as peroxynitrite, generated in macrophages by the reaction of nitric oxide with superoxide (McLean et al 2010;Prolo et al 2014). Moreover, NO reacts with cysteine thiols to form S-nitrosothiols (SNO), an effective inhibitor of Gram-positive bacteria and fungi (Finnen et al 2007;Cariello et al 2012). C. albicans is therefore exposed to a variety of toxic ROS, RNS, and RSS-related molecules and byproducts that it responds to in mechanistically distinct ways.…”
mentioning
confidence: 99%
“…It has been previously suggested that the antifungal actions of acidified nitrites are mediated by S ‐nitrosothiols formed by reaction of thiol groups in the toe‐nail with the acidified nitrites (Finnen et al . ). Another suggested explanation was that the combination of NO and reactive oxygen species produces intermediates, such as peroxynitrite, which are far more potent microbiocidal agents than their precursors (Fang ).…”
Section: Discussionmentioning
confidence: 97%
“…NO gas was shown to have antimicrobial activity against wide variety of bacteria (McMullin et al 2005;Ghaffari et al 2006) and fungi (Wang and Higgins 2005;Finnen et al 2007;Lazar et al 2008). It has also been reported that a short-term exposure to 50-500 ppm of NO was able to inhibit mycelial growth, sporolation and germination of postharvest horticulture fungi (Lazar et al 2008).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation